2018
DOI: 10.3389/fonc.2018.00634
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Score and Nomogram Combining Clinical and Immunohistochemistry Factors to Predict High ISUP Grade Clear Cell Renal Cell Carcinoma

Abstract: Objective: The International Society of Urological Pathology (ISUP) has proposed a grading system to classify renal cell carcinoma (RCC). However, classification using biopsy specimens remains problematic and, consequently, the accuracy of a biopsy-based diagnosis is relatively poor. This study aims to combine clinical and immunohistochemical (IHC) factors for the prediction of high ISUP grade clear cell RCC (ccRCC) in an attempt to complement and improve the accuracy of a biopsy-based diagnosis.Methods: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…Clinical analysis showed that ccRCC patients with the PTEN mutation have a significantly poorer prognosis in survival and disease recurrence. All these results indicate the significance of the clinical practice of the PTEN mutation in ccRCC patients, consistent with some recent research (22, 23). The detection of tumor gene mutations has been applied to the clinic, which can help clinicians judge the prognosis of patients and effectively select better individualized treatment strategies.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical analysis showed that ccRCC patients with the PTEN mutation have a significantly poorer prognosis in survival and disease recurrence. All these results indicate the significance of the clinical practice of the PTEN mutation in ccRCC patients, consistent with some recent research (22, 23). The detection of tumor gene mutations has been applied to the clinic, which can help clinicians judge the prognosis of patients and effectively select better individualized treatment strategies.…”
Section: Discussionsupporting
confidence: 92%
“…Bioinformatics analysis generates large and complex biological data through the comprehensive use of biology, computer science, and information technology. Its rapid development, such as The Cancer Genome Atlas (TCGA) database, provides researchers with a more user-friendly and convenient platform, guiding the implementation of basic experiments [12, 13]. In 2013, Yoshihara et al calculated specific molecular biomarker expression in immune and stromal cells, and thus generated an ESTIMATE algorithm with immune/stromal/ESTIMATE scores to predict the TME [9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 , 20 ] In recent years, many studies on the prognostic nomograms of ccRCC have been reported. [ 21 23 ] Also, a previous study has reported a predictive nomogram with immune-associated gene signature for ccRCC patients. [ 24 ] However, these studies on prognostic nomograms for ccRCC did not involve immune scores which can reflect the extent of immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%